308 EVALUATION OF A CD-ROM BASED INTERACTIVE EDUCATIONAL TOOL FOR MEDICAL STUDENTS ROTATING THROUGH PEDIATRICS. (1st January 2005) - Estrada, B.
Abstract : Purpose: An interactive, CD-ROM based educational program which allows medical students to perform virtual pediatric rounds has been developed at the University of South Alabama. This program contains virtual three-dimensional characters which play the role of hospital staff. Information about clinical cases and disease processes is provided to students by these characters. In addition clinical signs and medical procedures are presented utilizing multimedia. The program provides questions and feedback on disease diagnosis, treatment and related procedures. The conditions included in the program were congenital heart disease, childhood obesity, diabetes, fever, meningitis, stridor, gastroenteritis, immunizations, leukemia, intussusception and pneumonia. This abstract reports the evaluation of this program as an educational tool during the pediatric clerkship. Methods: At the beginning of their third year pediatric clerkship, each medical student received a copy of the program contained in a CD compatible with Windows 97 or higher. To evaluate the program's impact in the students fund of knowledge questionnaires were administered before and after its completion. Areas evaluated included diagnosis, treatment and medical procedures related to the disease conditions presented within the program. Chi-square analysis was used to determine the differences in the proportion of correct answers before and after the program's completion. Students were also asked to provide scores in a scale from 1 to 10 regarding the usefulness of this program in enhancing their education and its ease of utilization. Results: 25 medical students participated in the study. The following table demonstrates significant improvement in the proportions of correct answers on each of the evaluated areas before and after completion of the interactive program. The average score provided by students regarding enhancement of their pediatric education by the program was 7.8. The score provided regarding ease of utilization was 7.4. Conclusion: The use of this program by third year medical students is associated with knowledge base improvement in the diagnosis, treatment and procedures related to disease conditions discussed within this educational tool. This program enhances education during the pediatric clerkship and it is easy to use.